KEBIJAKAN FORMULATIF TINDAK PIDANA DI BIDANG PERLINDUNGAN MANGROVE BERBASIS KONSERVASI EKOSISTEM PESISIR - Elvany, Ayu Izza (Veritas et Justitia, 2024)
Indonesia boasts extensive mangrove forests spanning over three million hectares, yet these are steadily declining due to harmful activities such as deforestation and land degradation. As a shoreside ecosystem, mangroves in seaside zones are also threatened by destructive management practices in coastal areas and on islands. This research analyzes Indonesia’s current criminal (formulative) policy regarding offences against mangrove conservation as part of offshore ecosystems and proposes a sustainable, approach-based formulative policy to promote mangrove sustainability in Indonesia’s coastal zones. This is doctrinal legal research, wherein the proposed legal issues are analyzed using both statutory and conceptual approaches. The findings indicate that the formulative policy regarding offences against mangrove conservation, specifically Article 73 paragraph (1) letter b and paragraph (2) of Law Number 1 of 2014 concerning Amendments to Law Number 27 of 2007 on Management of Coastal Areas and Small Islands, does not align with the sustainability principle that underpins coastal ecosystem conservation, including mangroves. The study highlights the need to amend the policy by explicitly incorporating corporate criminal liability and reconstructing the sentencing framework based on restorative justice and deterrence theory. These changes aim to strengthen criminal law as a last resort (‘ultimum remedium’) for protecting mangrove sustainability and conserving coastal ecosystems.